جزئہ ت ح ق ی اامعتسل اک ق : وہفمم، احلطصمت اور رقآن ت ف س ملعِ ی The Science of Tafsīr: A Research Study on Its Meaning, Terminology, and Qur’ānic Usage - Dr. Zobia Parveen (jihat-ul-islam, 2024)
Tafsīr is a fundamental Islamic science that seeks to explain the meanings, implications, and wisdom embedded in the verses of the Holy Qurʾān. This paper explores the linguistic roots and terminological definitions of Tafsīr, examining how it has been understood, employed, and explained by classical and contemporary scholars. The Arabic root "f-s-r" connotes explanation, clarification, and unveiling of hidden meanings. The study reviews various definitions and highlights that Tafsīr is not simply a literal translation but an intellectual effort to elucidate divine meanings by employing auxiliary disciplines such as Arabic grammar, rhetoric, context (asbāb al-nuzūl), abrogation (nāsikh wa mansūkh), and readings (qirāʾāt). Additionally, this paper presents a critical analysis of the Qurʾānic usage of the term Tafsīr, noting that it appears once explicitly in Sūrat al-Furqān, and multiple times in synonymous forms such as bayān, tabyīn, tafsīl, kashf, and sharḥ. These synonyms, frequently employed in both the Qurʾān and Hadīth, emphasize the broader function of explanation and detailed interpretation. The research identifies thematic and terminological parallels between Qurʾānic and prophetic usage of these terms, showcasing their shared objective—to uncover divine intent. The aim of the study is to consolidate classical views and lexicons, thereby offering a comprehensive understanding of the concept of Tafsīr from its linguistic origin to its theological application. This provides foundational insights for scholars, students, and readers of the Qurʾān who seek deeper engagement with its meanings.